Pay Satisfaction, Job Satisfaction and Turnover Intent - Singh, Parbudyal; Loncar, Natasha (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2010)
The purpose of this paper was to examine the relationships among pay satisfaction, job satisfaction, and turnover. While there is a fairly large body of literature on pay satisfaction/dissatisfaction-turnover relationship, there are reasons to expect different outcomes in occupations – such as social work and nursing – where job satisfaction, versus pay, may be of equal, if not greater importance. Essentially, it may be argued that in these sectors, workers are driven more by job satisfaction rather than their paychecks. Yet, there is little empirical research on this issue; thus, a primary purpose of this study is to address this research need. This study will add to the recent research that has focused on key human resources management and industrial relations issues related to the nursing profession in Canada. Furthermore, many studies use a unidimensional measure of pay satisfaction even though the literature suggests that there are better measures. Using a four-dimensional instrument in this study, we improve on past practices.Using a sample of 200 nurses in a unionized hospital in Ontario to test our hypotheses, we found support for both (viz., 1. The four pay dimensions will affect turnover intent differently; and 2. Job satisfaction will add incrementally to the explained variance in the pay satisfaction-turnover relationship). The findings support the contention that nurses may be more motivated by their jobs, versus their pay. The findings may be good news for organizations that want to better manage labour costs. There are different ways for hospitals to improve their workplace environment in order to increase satisfaction with intrinsic job factors and reduce turnover.